Harmonic reduction in a renewable energy islanded microgrid with fuzzy PID controller - S.Srivatchan, N; P.Rangarajan, Dr (International Journal of Engineering and Technology, 2018)
Power sharing in an Islanded microgrid is not straight forward due to load variations as well as variable nature of Renewable En-ergy sources. This unequal power sharing leads to circulating currents, load imbalance and increased harmonic content. Traditional droop controller provides simple control for real power sharing without communication link, but they suffer from inaccurate reactive power sharing. To overcome the inherent drawback of traditional droop controller, this paper proposes cascaded H-bridge (CHB) multilevel inverter. CHB multilevel inverter provide increased output voltage, there by improves power quality. The Fuzzy Logic Con-troller provides simple and accurate control to CHB multilevel inverter. The proposed system is simulated in MATLAB Simulink Envi-ronment. This scheme provides closed loop control of DG units, in turn improves reactive power sharing between DG units, and thereby effectively reduces total harmonic distortion during islanding. The main focus of the paper is in power sharing issue on har-monic currents. The simulation results are verified with experimental microgrid hardware.Â Â